2015
DOI: 10.1016/j.gdata.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease associated transcription factor TCF21 regulates smooth muscle precursor cells that contribute to the fibrous cap

Abstract: TCF21 is a basic helix–loop–helix transcription factor that has recently been implicated as contributing to susceptibility to coronary heart disease based on genome wide association studies. In order to identify transcriptionally regulated target genes in a major disease relevant cell type, we performed siRNA knockdown of TCF21 in in vitro cultured human coronary artery smooth muscle cells and compared the transcriptome of siTCF21 versus siCONTROL treated cells. The raw (FASTQ) as well as processed (BED) data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…In addition, Tcf21 has been implicated in fibrous cap formation in coronary atherosclerotic diseases and in focal segmental glomerulosclerosis in kidney . Experiments using cardiovascular smooth muscle cells indicated that Tcf21 directly bound to the promoter regions of Acta2 and Pdgfrb genes and suppressed expression of Acta2 , Pdgfrb , and Col1a1 . From these findings, Tcf21 is considered to be a key molecule that regulates the progression of fibroproliferative diseases and thus could be a common target for antifibrotic therapy in different organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Tcf21 has been implicated in fibrous cap formation in coronary atherosclerotic diseases and in focal segmental glomerulosclerosis in kidney . Experiments using cardiovascular smooth muscle cells indicated that Tcf21 directly bound to the promoter regions of Acta2 and Pdgfrb genes and suppressed expression of Acta2 , Pdgfrb , and Col1a1 . From these findings, Tcf21 is considered to be a key molecule that regulates the progression of fibroproliferative diseases and thus could be a common target for antifibrotic therapy in different organs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Tcf21 plays critical roles in embryonic development and differentiation of specific types of mesenchymal cells, such as cardiac fibroblasts, renal podocytes, and pulmonary lipofibroblasts . In addition, Tcf21 has been implicated in fibrous cap formation in coronary atherosclerotic diseases and in focal segmental glomerulosclerosis in kidney . Experiments using cardiovascular smooth muscle cells indicated that Tcf21 directly bound to the promoter regions of Acta2 and Pdgfrb genes and suppressed expression of Acta2 , Pdgfrb , and Col1a1 .…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that Tcf21 expressing cells migrate into the forming atherosclerotic lesion and contribute to the fibrous cap 187 . Further studies are needed to investigate how lack of TCF21 contributes to lesion size and composition.…”
Section: Examples Of Functional Genomics At Selected Cad Gwas Locimentioning
confidence: 63%
“…40 GTPase proteins involved in cell growth and differentiation, and high expression of MRAS has been found in heart tissue. 44,45 Rs17609940 is located in the intron region of ANKS1A at chromosome 6. 44,45 Rs17609940 is located in the intron region of ANKS1A at chromosome 6.…”
Section: Discussionmentioning
confidence: 99%